CNN‐based received signal strength prediction: A frequency conversion scheme - Siyi Huang; Xingqi Zhang (Electronics Letters, 2023)
Abstract To support the design and deployment of emerging high‐frequency wireless systems in various applications such as intelligent transportation, advanced received signal strength (RSS) simulation tools for radio coverage prediction are needed. In railway transportation, the vector parabolic equation (VPE) method is a commonly used approach for radio wave propagation modelling in large guiding structures such as tunnels. However, running VPE simulations at high frequencies in such an environment is computationally expensive, as the discretization parameters are closely related to the wavelength. In this letter, the authors propose a convolutional neural network‐based model that can efficiently provide RSS prediction at high frequencies by leveraging data obtained from VPE simulations at a lower frequency as an anchor. This proposed model can significantly improve the efficiency of VPE for high‐frequency RSS predictions and has been validated against conventional VPE in various tunnel cases.